2018
DOI: 10.1111/wre.12300
|View full text |Cite
|
Sign up to set email alerts
|

Defining the habitat niche of Alopecurus myosuroides at the field scale

Abstract: SummaryThe distribution of Alopecurus myosuroides (black‐grass) in fields is patchy. The locations of these patches can be influenced by the environment. This presents an opportunity for precision management through patch spraying. We surveyed five fields on various types of soil using a nested sampling design and recorded both A. myosuroides seedlings in autumn and seed heads in summer. We also measured soil properties at those sampling locations. We found that the patches of seed heads within a field were sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 9 publications
(19 reference statements)
1
36
0
Order By: Relevance
“…Similarly, ecological factors may interact in spatially explicit ways, for example, predators affect weed distribution and density, just as weed distribution and density also influences predator population density [88]. In addition, environmental and ecological drivers of spatial heterogeneity may interact, as not only are weeds affected by soil characteristics [89], but they can themselves, in turn, affect the quality of the soil [90][91][92]. Persistent weedy patches will influence both future weed invasions, and crop yields.…”
Section: Interactionsmentioning
confidence: 99%
“…Similarly, ecological factors may interact in spatially explicit ways, for example, predators affect weed distribution and density, just as weed distribution and density also influences predator population density [88]. In addition, environmental and ecological drivers of spatial heterogeneity may interact, as not only are weeds affected by soil characteristics [89], but they can themselves, in turn, affect the quality of the soil [90][91][92]. Persistent weedy patches will influence both future weed invasions, and crop yields.…”
Section: Interactionsmentioning
confidence: 99%
“…The observed patchy pattern is the result of heterogeneous environmental conditions (e.g., soil spatial heterogeneity, microclimatic conditions) [8,9], or of processes such as the dispersal rate and distance from the parent plant [10], competition between species or facilitation processes in which species mitigate the environmental condition and thus benefit other species (e.g., nurse plants [11]), or a combination of these factors [12,13]. Patchiness in weed distributions might also reflect differences in local management actions (e.g., seed dispersal and movement by farm equipment [14] and direction of tillage and irrigation furrows [15]).…”
Section: Introductionmentioning
confidence: 99%
“…However, the decreasing number of chemical products available for use, and increasing economic and environmental pressures to reduce herbicide use puts a growing emphasis on the optimisation of current techniques and finding alternative approaches (Grundy, 2003). The within-field distribution of A. myosuroides is patchy (Wilson and Brain, 1991, Krohmann et al, 2006, Metcalfe et al, 2016, Metcalfe et al, 2018b) and as such this presents an opportunity for site-specific management.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the patchy distribution of A. myosuroides in fields can be related to variation in soil properties (Holm et al, 1997, Lutman et al, 2002, Murdoch et al, 2014, Metcalfe et al, 2016, Metcalfe et al, 2018b), particularly soil organic matter, pH, and water. Metcalfe et al (2018b) demonstrated that these relationships are strongest at coarse scales (>20 m), making them ideal for the implementation of precision management. This provides a basis upon which to identify weed vulnerable zones within fields for this species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation